Interconnection of rhethoric and music art - Oliinyk, Oleksandr L. (Linguistics and Culture Review, 2021)
From the beginning of its formation, rhethoric had an undeniable impact on music. It mostly concerns rhethoric being the basis for the construction of a musical sound continuum which is valuable for developing the skills of improvisation. The process of transformation of the basic elements of rhetoric was presented. The authors mentioned the initial positions of rhetoric and their connection with music art. Ways of realization of traditional parts of rhetoric (Inventio, Dispositio, Elocutio, Memoria, Pronuntatio) in music were studied. Attention was paid to stringed and plucked instruments, including domra as an academic folk instrument, and possible ways to use rhetorical components. The process of academization of domra was characterized. It led to aggravating the problem of improvisation in the presentation of material. The intensity of the artistic component in the creative construction of the instrumental playing and in the essence of the artist’s performing position was determined.